Realized distribution patterns of crowned lemurs (Eulemur coronatus) within a human‐dominated forest fragment in northern Madagascar - Mercado Malabet, Fernando; Peacock, Heather; Razafitsalama, Jeremi; Birkinshaw, Christopher; Colquhoun, Ian (American journal of primatology, 2020)
Due to the impact of anthropogenic activities on forest extent and integrity across Madagascar, it is increasingly necessary to assess how endangered lemur populations inhabiting human‐dominated forest fragments can effectively sustain themselves ecologically. Our research addresses this concern by exploring how the distribution patterns of a small population of crowned lemurs (Eulemur coronatus), occupying a degraded forest fragment at Oronjia Forest New Protected Area in northern Madagascar, are impacted by the availability of key ecological and anthropogenic factors. We hypothesize that the distribution of E. coronatus within the fragment is limited by the availability of critical ecological resources and conditions and the intensity of anthropogenic features and activities. To examine this, we used MaxEnt to develop a species distribution model using presence‐only occurrence records and 10 independent background covariates detailing the site's ecological and anthropogenic aspects. The results indicate that the realized distribution patterns of E. coronatus within human‐dominated forest fragments are strongly associated with sections of forest that contain sparsely and sporadically distributed resources, such as freshwater and continuous hardwood vegetation. We conclude that the distribution of E. coronatus at Oronjia is shaped by their need to maximize foraging opportunities in a degraded forest landscape where they are subject to both environmental and anthropogenic stressors. Realized habitat distribution of crowned lemurs (Eulemur coronatus) in Oronjia Forest New Protected Area, northern Madagascar. Research Highlights The distribution of E. coronatus within human‐dominated forest fragments varies in accordance with the structure and quality of the forest and the patchy distribution of resources such as freshwater. The modeled distribution patterns of E. coronatus are not constrained by the proximity of villages and farms in the vicinity of their occupied forest habitat. Human‐dominated forest fragments pose suitable opportunities for the conservation of lemurs with flexible ecologies as long as conservation authorities manage the availability of patchily distributed resources.